224k views
1 vote
-3x + 3y =3
-5x + y =13 Solve as a whole number

User Chrsi
by
4.6k points

2 Answers

0 votes

Answer:

X = 3 x − 14

y = − x + 5

Explanation:

Solve for the first variable, then substitute the result into the other equation.

User Leonardo Costa
by
5.1k points
2 votes

Answer:

x = -3, y = -2

(-3, -2)

Explanation:

-3x + 3y = 3

-5x + y = 13

-5x + y = 13

+5x +5x

y = 5x + 13

-3x + 3(5x + 13) = 3

-3x + 15x + 39 = 3

12x + 39 = 3

- 39 -39

12x = -36

/12 /12

x = -3

Now, we solve for y:

-5x + y = 13

-5(-3) + y = 13

15 + y = 13

-15 -15

y = -2

(x, y) -> (-3, -2)

Hope this helps!

-3x + 3y =3 -5x + y =13 Solve as a whole number-example-1
User Mikemeli
by
4.1k points